2021
DOI: 10.1002/tox.23305
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocrenatidine inhibits head and neck cancer cells invasion and migration by modulating JNK1/2 and ERK1/2 pathway and decreases MMP‐2 expression

Abstract: Head and neck cancer is associated with poor prognosis because of its highly metastatic nature. For the better management of head and neck cancer patients, it is very important to diagnose the cancer at an early stage, as well as to prevent the rapid spread of cancer either through direct invasion or lymphatic metastasis. In present study, the effect of dehydrocrenatidine, which is a beta‐carboline alkaloid found in the medicinal plant Picrasma quassioides, on human head and neck cancer metastasis was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Five random fields were captured from each group using a microscope (Nikon, Tokyo, Japan) and cell numbers were counted. For cell migration assay, the procedures were the same as above expect that no Matrigel was precoated in the upper chamber 35–37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five random fields were captured from each group using a microscope (Nikon, Tokyo, Japan) and cell numbers were counted. For cell migration assay, the procedures were the same as above expect that no Matrigel was precoated in the upper chamber 35–37 …”
Section: Methodsmentioning
confidence: 99%
“…For cell migration assay, the procedures were the same as above expect that no Matrigel was precoated in the upper chamber. [35][36][37]…”
Section: Transwell Assaymentioning
confidence: 99%
“…Velmurugan and team 89 studied dehydrocrenatidine in vitro using FaDu, SCC9, and SCC47 cell lines. The investigators found that treatment with dehydrocrenatidine reduced cellular viability, motility, migration, and invasion in all three cell lines.…”
Section: Phytochemicals In Oral Cancer Researchmentioning
confidence: 99%
“…Regarding apoptosis, dehydrocrenatidine augmented phosphorylation of p38 mitogen-activated protein kinase (MAPK), c-Jun N-terminal kinase 1 (JNK-1) also known as MAPK8, JNK-2 (MAPK9), ERK-1, and ERK-2, and Akt, as well as decreased expression of Fas, Fasassociated death domain protein (FADD), tumor necrosis factor (TNF)-receptor associated death domain protein (TEADD), TNF-receptor 1 (TNFR1), and receptor-interacting protein (RIP) expression. Furthermore, there was an increase in decoy receptor 2 (DcR2) and death receptor 5 (DR5) expression, Bax, Bak, truncated BH3-interacting domain death agonist (tBid) and Bcl-2, as well as a decrease Bcl-2 and B-cell lymphoma-extra-large (Bcl-xL).Velmurugan and team89 studied dehydrocrenatidine in vitro using FaDu, SCC9, and SCC47 cell lines. The investigators found that treatment with dehydrocrenatidine reduced cellular viability, motility, migration, and invasion in all three cell lines.…”
mentioning
confidence: 99%
“…Moreover, matrix metalloproteinases (MMPs) are key executors of tumor invasion, which are the downstream products of ERK1/2 signals. They inhibit tumor metastasis by degrading the fibrous or stromal tissue surrounding the tumor, thus limiting the cancer cell migration throughout the body [20][21][22][23]. Hence, FGFs, ERK1/2 and MMPs are key checkpoints for cancer suppression.…”
Section: Introductionmentioning
confidence: 99%